The challenges of teaching architectural project in the 21st century - Alba-Dorado, María Isabel (NIRD URBAN-INCERC, 2023)
In recent years we have witnessed a series of changes that make it both necessary and urgent to redefine the limits of the architectural discipline, and in particular those of its teaching. The traditional profile of the architect as a builder has been radically transformed and has evolved towards other scenarios. The traditional teaching tools and procedures do not offer a response to the professional reality that the architect must assume in the face of the new approaches, services and considerations that contemporary society demands for this century. The aim of this article is to offer a reflection, from an educational perspective, on the challenges that the teaching of architectural project must face in order to provide future architects with the tools that will allow them to both approach new professional scenarios and respond to untested problems and unforeseen situations in a complex world. Training professionals to think for themselves with a critical and innovative spirit, encouraging the practice of creative and flexible thinking that enables them to define proposals and make imaginative decisions, developing work skills in co-production and co-creation environments or incorporating digital technology in the training of professionals are some of the challenges that this research addresses.
Keywords: Arquitectura - Estudio y enseñanza; Creativity; Critical thinking; Design process; Collaborative practices; Digital technologies